2020
DOI: 10.3390/microorganisms8040543
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Origin of Planktonic Protists in an Ancient Lake

Abstract: Ancient lakes are among the most interesting models for evolution studies because their biodiversity is the result of a complex combination of migration and speciation. Here, we investigate the origin of single celled planktonic eukaryotes from the oldest lake in the world—Lake Baikal (Russia). By using 18S rDNA metabarcoding, we recovered 1414 Operational Taxonomic Units (OTUs) belonging to protists populating surface waters (1–50 m) and representing pico/nano-sized cells. The recovered communities resembled … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 79 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…To study the diversity and relative abundance of microbial eukaryotes in Lake Baikal plankton, we concentrated cells in the 0.2–30 μm diameter fraction by successive filtration steps. This fraction thus integrated pico‐ (0.2–2 μm), nano‐ (2–20 μm) and small microplankton (20–30 μm), covering a wider protistan spectrum than some previous comparative studies (Annenkova et al ., 2020). We purified DNA and massively sequenced (MiSeq Illumina, 2 × 300 bp) multiplexed 18S rRNA gene V4‐region amplicons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the diversity and relative abundance of microbial eukaryotes in Lake Baikal plankton, we concentrated cells in the 0.2–30 μm diameter fraction by successive filtration steps. This fraction thus integrated pico‐ (0.2–2 μm), nano‐ (2–20 μm) and small microplankton (20–30 μm), covering a wider protistan spectrum than some previous comparative studies (Annenkova et al ., 2020). We purified DNA and massively sequenced (MiSeq Illumina, 2 × 300 bp) multiplexed 18S rRNA gene V4‐region amplicons.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Annenkova et al . (2020) determined the community structure of small protists (0.45–8 μm cell‐size fraction) from surface waters (1–15‐50 m) across the lake via 18S rRNA gene V4‐region metabarcoding using higher throughput sequencing approaches (Illumina MiSeq) and suggested that some clades within known protist groups might be endemic. Nonetheless, we still lack a comprehensive view about how microbial eukaryotes distribute in the lake plankton, across basins and throughout the complete water column and, crucially, which are the most influential parameters determining community structure.…”
Section: Introductionmentioning
confidence: 99%
“…The exception might be Apicomplexa, where some studies have suggested that it is only found in very low abundance in lake water [57]. However, others have described members of Apicomplexa as freshwater parasites [75,76], and their relatively high abundance in all four sediment profiles suggests that their origin is the water column. It is noticeable that the molecular signal from certain microbial eukaryotic groups with an aquatic origin, such as Cryptophytes and Haptophytes, might not be well-preserved in sediments [68].…”
Section: Reliability Of the Sedimentary Dna Signal To Unravel Past Lamentioning
confidence: 99%
“…As dinophytes constitute a considerable fraction of the plankton and play an important role in the global aquatic ecosystem, HTS studies have detected their DNA from waters sampled from the polar regions through to the tropics (Annenkova et al. 2020; Decelle et al. 2018; Elferink et al.…”
mentioning
confidence: 99%
“…All known dinophytes are from marine or freshwater environments (Adl et al 2019), except maybe the unarmored (athecate) Esoptrodinium (Fawcett and Parrow 2014). As dinophytes constitute a considerable fraction of the plankton and play an important role in the global aquatic ecosystem, HTS studies have detected their DNA from waters sampled from the polar regions through to the tropics (Annenkova et al 2020;Decelle et al 2018;Elferink et al 2017;Giner et al 2020;Le Bescot et al 2016;Lentendu et al 2018;de Vargas et al 2015). HTS studies have also detected DNA of dinophytes in terrestrial environments (Bates et al 2013;Geisen et al 2015;Mah e et al 2017;Venter et al 2017;Voss et al 2019), although they are not expected to be there.…”
mentioning
confidence: 99%